INTEGRATING MINDFULNESS-BASED EDUCATION TO REDUCE ANXIETY DISORDERS AMONG ADOLESCENT PENCAK SILAT ATHLETES: A QUASI-EXPERIMENTAL STUDY - Mohammad Aldi Nuril Asyari; Weni Kurnia Rahmawati; Nailul Fauziyah (CV. TOTUS TUUS, 2025)
Anxiety disorders represent one of the most prevalent mental health challenges globally, with athletes—especially those in high-pressure sports such as pencak silat—facing unique vulnerabilities due to the intense physical, psychological, and cultural demands of competition. This study aimed to evaluate the effectiveness of mindfulness-based interventions in reducing anxiety disorder symptoms among adolescent pencak silat athletes at Cempaka Putih Ranting Jombang, Indonesia. Employing a quasi-experimental, one-group time series design, the research involved seven athletes who underwent a structured mindfulness program delivered over three weeks. Data were collected through validated self-report questionnaires (BAI and SCAT) and qualitative interviews, measured at four pre- and four post-intervention points. The results demonstrated a statistically significant reduction in anxiety symptoms across cognitive, emotional, somatic, and behavioral domains, with athletes reporting increased self-regulation, improved emotional stability, and enhanced overall well-being. The findings highlight the substantial benefits of integrating mindfulness practices into athlete training routines, especially in culturally rooted martial arts environments where traditional mental health resources may be limited or stigmatized. This research contributes to the literature by providing robust, contextually grounded evidence of mindfulness efficacy for adolescent martial artists—a group largely underrepresented in sports psychology research. For practical implementation, sports organizations and coaches are encouraged to incorporate mindfulness strategies within athlete development programs to support psychological resilience and performance. Future research should employ larger samples, randomized controlled designs, and extended follow-up periods to assess the long-term effects and broader applicability of mindfulness interventions in diverse athletic and cultural contexts.